2015
DOI: 10.1371/journal.pone.0128958
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Safe Medication Administration to Hospital Inpatients: A Mixed Methods Study of Nurses’ Medication Administration Processes and Systems (the MAPS Study)

Abstract: ContextResearch has documented the problem of medication administration errors and their causes. However, little is known about how nurses administer medications safely or how existing systems facilitate or hinder medication administration; this represents a missed opportunity for implementation of practical, effective, and low-cost strategies to increase safety.AimTo identify system factors that facilitate and/or hinder successful medication administration focused on three inter-related areas: nurse practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 31 publications
4
90
0
5
Order By: Relevance
“…Environmental context and resources proved key barriers to nurses’ appropriate use of EMMS. Other studies have highlighted barriers such as design shortcomings [21, 22, 2628, 30, 66], time pressure and competing demands. The availability, size and characteristics of COWs and log-in time influenced nurses’ likelihood of taking them to the bedside, leaving unattended COWs logged in, or signing off medications before administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Environmental context and resources proved key barriers to nurses’ appropriate use of EMMS. Other studies have highlighted barriers such as design shortcomings [21, 22, 2628, 30, 66], time pressure and competing demands. The availability, size and characteristics of COWs and log-in time influenced nurses’ likelihood of taking them to the bedside, leaving unattended COWs logged in, or signing off medications before administration.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial that ergonomic design improvements are based on assessment of workflow and environment and pilot-tested prior to implementation [29, 32]. McLeod and colleagues reported, for example, nurses preferred a smaller tablet over a COW but found that because the tablet was too small, medications were signed off at the desktop [22]. Previous findings highlight the benefits of point-of-care access to information about test results, medication administration instructions and patient information [68, 69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study of (McLeod, Barber, & Franklin, 2015) on the application of the principle of the six rights in the administration of medications by nurses pointed out that nurses are not applying the principle of the six rights application in medication delivery as a whole. There were 81.4% of nurses are already doing the right dose, 70% of nurses are already doing on time, 5.7% of nurses do not invoke the name of the patient when giving medications, 98.9% of nurses have not been applying the principle of the right way, 10% of nurses is not appropriate documentation and to note that 100% of nurses is not appropriate medication.…”
Section: Introductionmentioning
confidence: 99%